Assessment of sestrin 2 as a sepsis marker and predictor of disease severity - Osman Baspınar; Derya Kocer; Kaniye Aydın; Oguzhan Sıtkı Dizdar (The Aging Male)
Introduction Sestrin 2 is considered a stress-inducible antioxidant protein. This study was aimed to evaluate sestrin 2 in subjects with sepsis, and its correlation with clinical severity and mortality.Methods Sepsis and control group patients were followed from admission to discharge. A blood sample was taken at admission for determination of serum sestrin 2 level.Results Of the total 42 patients with sepsis, there were 25 females and the mean age was 74.9 years. The sestrin 2 levels were significantly higher in the sepsis group. The optimum sestrin 2 cut-off point of ≥3.13 ng/mL had 95.2% sensitivity and 71.4% specificity for sepsis (p < .001). Sestrin 2 levels were higher in patients who needed renal replacement therapy (p = .018), patients who needed vasopressor therapy (p = .001) and patients with organ dysfunction (p = .002). The sestrin 2 level was significantly correlated with Acute Physiology and Chronic Health Evaluation (APACHE) II score, Nutrition Risk in the Critically Ill (NUTRIC) Score, C-reactive protein and albumin. Sestrin 2 levels were not associated with 30 d mortality in sepsis patients.Conclusions Sestrin 2 was significantly higher in the sepsis patients and associated with sepsis related adverse clinical outcomes. These results provided information concerning the clinical utility of sestrin 2.